Enfermer les contagieux et les contagieuses à Marseille pendant la peste de 1720 - Fleur Beauvieux (Criminocorpus)
The plague of Marseilles in 1720-1722 led to the emergence of a network of confinement facilities for the plague victims. This period of high mortality led to a redefinition of confinement at the beginning of the 18th century: being locked up became in part a punishment, well before the post-revolutionary laws that would institute this punishment. Although previous plagues in the 17th century had already seen the emergence of places of confinement such as the Refuge, this was out of all proportion to the significant increase seen in times of epidemics. These mobilities led to new gender relations, socio-familial reorganisations and a redefinition of the intimate. The establishments that were active during the epidemic allow us to study the institution of the Refuge and the complexity of the confinement of women and girls.